STUDY OF CHRONIC TOXICITY OF THE GLYPHOSATE HERBICIDE ON SEEDS OF PARSLEY, LETTUCE AND CORIANDER - NASCIMENTO, ANA PAULA DO; RODRIGUES, BRUNA; ROQUE, BRUNO R. F.; RISSI, CAROLINA DENARDI; FREITAS, DRIELLE; QUIMENTÃO, FERNANDA; HONÓRIO, GERSON; MARTINS, JÉSSICA RODRIGUES; SILVA, JOÃO HENRIQUE NASCIMENTO E; LUCCA, JOSIELE DE; et al. (Revista Brasileira de Engenharia de Biossistemas, 2009)
Glyphosate is an agrochemical from the group of phosphonates widely used as an herbicide. Althoughit kills almost any plant, it can be used to eliminate weeds during the growing season of commercialcrops resistant to glyphosate. This research aimed to evaluate the toxicological effects of the herbicideusing seeds of parsley (Petrosolium sativum), lettuce (Lactuca sativa) and coriander (Coriandrumsativum.) In the toxicological test was used twenty seeds each, dampened with glyphosate, evenlydistributed in containers with lids. The containers were left in a dry and airy place, and it was wateredonce a day for 5 days. It was possible to check the toxic effect in the germination and growth of theseeds provoked by the glyphosate, such as: for parsley (Petrosolium sativum) at concentrationsabove 90 mg.L-1, for lettuce (Lactuca sativa) seeds at concentrations above 4 mg L-1 and for coriander(Coriandrum sativum) seeds in concentrations above 12 mg L- 1. With these results it was possible toconclude that the seeds studied were very sensitive to glyphosate. Also, these seeds can be used asa reference for toxicity testing